(untitled) (مجلة الرازي الطبية, 2025)
Urinary tract infections (UTIs) are among the most prevalent bacterial infections, affecting all ages and ranging from uncomplicated cystitis to severe pyelonephritis. This study was conducted to determine the prevalence of uropathogens causing urinary tract infections (UTIs), their capacity for biofilm formation, and their antimicrobial resistance patterns in Misurata, Libya. A cross-sectional study was conducted at two medical centers in Misurata. A total of 40 patients clinically diagnosed with UTIs were included. Patient ages ranged from 5 to 88 years, and the majority of them were female (80%). All isolates were identified using standard microbiological techniques. Identified bacteria were subjected to biofilm detection using the Congo Red Agar (CRA) method, and antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method. Staphylococcus aureus (37.5%) and E. coli (32.5%) were the most predominant bacteria among UTI patients, followed by Coagulase-negative staphylococci (CONS) (15%), P. aeruginosa (7.5%), and Klebsiella spp. (5%) and Streptococcus spp. (2.5%). Biofilm formation on Congo Red Agar was observed for 40% of the isolates, with the highest frequency in P. aeruginosa (2/3; 66.7%), followed by S. aureus (8/15; 53.3%) and Klebsiella spp. (1/2; 50%). Antimicrobial susceptibility testing revealed variable resistance patterns, particularly to amoxicillin, nitrofurantoin, and ceftriaxone. Multidrug resistance was detected in several isolates, including E. coli, S. aureus, Pseudomonas spp., Klebsiella spp., and CONS. Although the sample size was small, the detection of pathogenic bacteria with biofilm-forming capacity and multidrug resistance represents a significant clinical concern and underscores the urgent need for ongoing antimicrobial resistance surveillance. Further studies with larger sample sizes and molecular characterization of resistance and biofilm-associated genes will provide deeper insight into the epidemiology of uropathogens in Libya and guide effective treatment strategies for UTI management.